(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
Aim: The aim of the study was to determine the influence of the size of permanent incisors on the appearance of the crowding of the anterior segment of dental arches. Materials and Methods: The study included 100 subjects, aged 13-25 years. All the examinees were divided into two groups. The first group comprised 50 subjects (25 males and 25 females) who had marked symptoms of crowding, especially in the anterior segment. The second group comprised 50 subjects (25 males and 25 females) with normal occlusion. The measurement was performed using a digital caliper, 0.01 mm of accuracy. The following parameters were examined: mesiodistal (MD) and labiolingual (LL) diameter of the maxillary and mandibular incisors. The index of the crown of the tooth was calculated using the formula (MD/LL)×100. Results: The results of this study show that the mesiodistal diameter and the index of the crown of upper and lower incisors has a significantly higher value in both male and female in crowding compared with normal occlusion. In this study, the higher values of the index of tooth crown in patients with crowding, may be due to greater mesiodistal diameter of teeth. Conclusion: The results of this study suggest that increased tooth size has a contributory role in dental crowding. Ban J Orthod & Dentofac Orthop, October 2012; Vol-3, No.1